A holistic approach to manufacturing systems modelling. (26th May 2009) - Delen, Dursun
The success (or mere survival) of today's enterprises depends on their managers making correct decisions to rapidly align organisational processes toward meeting and exceeding ever-changing needs and wants of the customer. In order to be successful managers need integrated information systems capable of supporting them throughout the decision-making lifecycle. These systems should be capable of using a wide variety of models along with the most current data and information stored in distributed locations, managed as critical organisational assets. This paper presents a holistic approach to such a manufacturing systems-modelling paradigm using a structured description capture method, called IDEF0.